Does democracy foster trust? - Helmut Rainer; Thomas Siedler (Institute for the Study of Labor (IZA), 2006)
The level of trust inherent in a society is important for a wide range of microeconomic and macroeconomic outcomes. This paper investigates how individuals' attitudes toward social and institutional trust are shaped by the political regime in which they live. The German reunification is a unique natural experiment that allows us to conduct such a study. Using data from the German General Social Survey (ALLBUS) and from the German Socio-Economic Panel Study (SOEP), we obtain two sets of results. On one side, we find that, shortly after reunification, East Germans displayed a significantly less trusting attitude than West Germans. This suggests a negative effect of communism in East Germany versus democracy in West Germany on social and institutional trust. However, the experience of democracy by East Germans since reunification did not serve to increase levels of social trust significantly. In fact, we cannot reject the hypothesis that East Germans, after more than a decade of democracy, have the same levels of social distrust as shortly after the collapse of communism. In trying to understand the underlying causes, we show that the persistence of social distrust in the East can be explained by negative economic outcomes that many East Germans experienced in the post-reunification period. Our main conclusion is that democracy can foster trust in post-communist societies only when citizens' economic outcomes are right.
Keywords: P51; Z13; 330; social trust; institutional trust; political regimes; Demokratie; Vertrauen; Nationale Einheit; Regionale Entwicklung; Deutschland